The role of the community pharmacist in optimising patients' inhaler use in asthma management - Buckley, Kathleen Niamh (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
The Asthma Insights and Reality in Ireland survey revealed that only 8% of those surveyed had controlled asthma, as defined by evidence-based guidelines. A detailed analysis of patients’ abilities to use their inhalation devices in the real-life setting and the effects of various educational interventions on inhaler technique determined the primary objective of this project, which was to investigate the role of the community pharmacist in optimising patients’ inhaler use. Prior to the design and implementation of a community pharmacist-led educational intervention it was essential to determine the opinions of the health-care professionals on the current state of asthma care in the primary care setting in Ireland, and to investigate if there were certain areas, considered important in asthma management, which were being neglected. The Asthma Society of Ireland and the Irish College of General Practitioners collaborated on the Demonstration Project, a project designed to investigate the barriers and facilitators to the implementation of best-practice asthma guidelines in primary care. The role of the pharmacist in asthma management was investigated prior to and after the commencement of the Demonstration Project. However, it became evident that community pharmacists had only limited involvement in this project and their role was poorly defined. Consequently, a community pharmacist-led educational intervention on inhaler technique was designed. It was considered essential to evaluate the impact of this intervention on all aspects of a patient’s health status; therefore, prior to implementing the intervention a quality of life instrument with good psychometric properties was determined.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin